Religious Message Abdullah Bin Umar Paraga In The Wayang Kekayon Khalifah - Lutfianto Lutfianto; Fahmy Lukman (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Puppet art is an art that is loaded with philosophical values. The presentation is packaged in an orchestral performance and is very collaborative, there are visual arts, dance arts, literary arts, and music (gamelan) arts. Everything is harmoniously integrated and in harmony with its physical and social architecture. Therefore, the interesting wayang art is used as a medium in education to present the spirit, impression, and moral message of students/students. This creation or creation uses the Artistic Research method and the Practice Based Research thinking scheme, focusing on contemporary artworks. It aims to create knowledge through practice-based expression. How to realize the design of a work of art creation using cow or buffalo leather media can reflect a moral message through existing decorations and ornaments using an aesthetic approach and leather craft. The design of this leather craft produces an artifact in the form of the puppet gunungan paraga Abdullah bin Umar. In this work, the aesthetic effect that appears is a combination of decorations and ornaments as well as harmonious calligraphy of character names. So that this media can present beauty in conveying Abdullah bin Umar's message of religiosity.